Genotypic Detection of rcsB, afaB, fim Hgenes Coding Biofilm Production of Escherichia Coli Isolated from Pressure Ulcer - Abdul Kareem Al-Makhzoomy, Taghreed (International Journal of Psychosocial Rehabilitation, 2020)
Pressure ulcers, or bedsores, are localized injuries to the skin and/or underlying tissue that commonly commonlyhappen over a bony prominence. Infected pressure ulcers pose a great risk when left untreated; they can affect other body systems. The most common bacterial types found in infected ulcers are Pseudomonas aeruginosa , Escherichia coli , Staphylococcus aureus, and Staphylococcus hemolyticus. Therefore, 82 swabs were collected from patients suffering from bed ulcers and admitted to Al-Sader Medical City and Al-Hakim General Hospital during the term from November 2018 to February 2019. The specimens were refined in suitable media (MacConkey agar and nutrient agar). After the incubation period, the result revealed that 119 bacterial isolates were isolated and identified according to the Vitek-2 system; 57 (47.9%) of the isolates were gram positive, and 62 (52.1%) were gram negative. The gram negative were represented by 25 isolates of Escherichia coli, 12 of Klebsiella pneumoniae, 14 of Pseudomonas aeruginosa, 9 isolates of Proteus mirabilis, and one isolate each of Serratia ficaria and Pseudomonas fluorescens. Genetically, study the rcsB, afaB, and fimH genes encoding biofilm formation that are associated with the pathogenicity of Escherichia coli by using the PCR technique. The result of the present study reported that the fimH gene was found in 23 (92%) isolates of Escherichia coli, the afaB gene was found in 19 (76%) of Escherichia coli isolates, and the rcsB gene was found in 20 (80%) of Escherichia coli isolates.